1987
DOI: 10.1002/clc.4960101201
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmogenic properties of disordered breathing during sleep in patients with cardiovascular disorders

Abstract: Summary: The purpose of this study was twofold: to establish an ECG respiration monitoring system, and to evaluate the clinical usefulness of this system. Our purpose was to determine how many patients with cardiovascular disorders may have unrecognized sleep apnea and whether such apneic episodes are an important cause of cardiac arrhythmias. The study group included 81 patients, age range 40-95 years, and 13 healthy males, age range 52-72 years. The 24-h ECG respiration recordings were obtained with the two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…There is an association between habitual snoring and/or obstructive sleep apnea and cardiac arrhythmias (Gillis, 1985;Peiser et al, 1985;Otsuka et al, 1987;Shepard, 1992;Adlakha and Shepard, 1998;Kohler et al, 1998;Sanner et al, 1999;Porthan et al, 2004).…”
Section: Heart Diseasementioning
confidence: 99%
“…There is an association between habitual snoring and/or obstructive sleep apnea and cardiac arrhythmias (Gillis, 1985;Peiser et al, 1985;Otsuka et al, 1987;Shepard, 1992;Adlakha and Shepard, 1998;Kohler et al, 1998;Sanner et al, 1999;Porthan et al, 2004).…”
Section: Heart Diseasementioning
confidence: 99%
“…In the early days of sleep research, heart block (second and third degree atrioventricular block [II° and III° AV block]), sinus arrest or sinuatrial block were thought to be highly prevalent in patients with OSA, and the reported incidence ranged between 18% and 50%[167, 235]. More recent data of unselected patients treated in a sleep laboratory revealed prevalence rates between 7% and 13%[15, 22, 142].…”
Section: Heart Blockmentioning
confidence: 99%
“…There was cardiac disorders, but patients with left nean ejection frac-ventricular impairment were not specifically > III arrhythmias included. 8 Dark et al showed an improvement tith grade <III in oxygen saturation after treatment of heart ompared with 27 failure in six patients with left ventricular dysfunction, but no analysis of arrhythmia was undertaken. 9 Hanly et al carried out oximetry IYTHMIAS AND in 10 outpatients with chronic heart failure and showed poor quality of sleep with frequent dips n between severity and arousals, but again arrhythmias were not de > III v Lown analysed.…”
Section: Electrocardiographic Monitoringmentioning
confidence: 99%